Ozone hole time series ... - Van Roozendael, Michel (Royal Belgian Institute for Space Aeronomy, 2023)
Time series of the October mean ozone vertical column above Antarctica. The dataset behind those images was developed within the ESA Climate Change Initiative Programme (https://climate.esa.int/en/projects/ozone/) and is operationally distributed by the [EU Copernicus Climate Change Service](https://cds.climate.copernicus.eu/cdsapp#!/dataset/satellite-ozone-v1?tab=overview) ...